Congestion Control Using TFC and TFR In Common Channel Signaling System#7 (SS7) At Message Transfer Part-Level 3 - K. Prabhakar; Paul, P. John; kumar, B.P.Pradeep (International Journal of Psychosocial Rehabilitation, 2020)
Signalling refers to the exchange of information between the call components required to maintain and provide the call service. The communication between telephones-switches in public telephone networks with different set of protocols are known as Signalling System Number 7 (SS7 or CCS#7). The function of SS7 are call control, maintenance capabilities based on office telephone network and network management remotely. The telephone networks are vulnerable to attacks and congestion occurring in the telecommunication. In telecommunication network( BSNL concerning) a failure of links and exchanges i.e, out of service of links and outage of exchanges. In addition, congestion situations may cause failure of single links. Therefore, to avoid such problems, “Congestion Control at MTP-L3 (Message Transfer Part-Layer3)” is used for controlling the traffic occurring at the MTP-L3 layer using Transfer Control (TFCs) and transfer restricted mechanism (TFRs). The “Secured Tracking Devices (STD)” is used for secured transmission of voice and data in the telecommunication by identifying the attackers. Hence, the “CC at MTP-L3 STD” methodology provides better results by varying Number of nodes and energy consumption of existing “STD without TFCs/TFRs. The route reliability increases with decrease in network lifetime, end-to-end delay and Congestion Control.